PENGARUH PARAMETER PROSES ELEKTRODEPOSISI TERHADAP PENENTUAN BERAT ISOTOP 235U DALAM PEB U3Si2/Al PASCA IRADIASI - Yanlinastuti, Yanlinastuti; Boybul, Boybul; Ginting, Aslina Br.; Anggraini, Dian (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Electrodeposition process for determination of 235U isotope is affected by current, contact time, feed volume and type of buffer solution. The aim of this research is to obtain optimum parameter of electrodeposition process for 235U determination in U3Si2/Al irradiated fuel plate. Electrodeposition process is done by some variation of parameters, that are the current 1; 1.2; and 1.4 ampere with variation of time 1; 1.5; 2.0; 2.5 and 3.0 hours. The standard solution volume of 20% U3O8 are 100; 300; 500; 700 µL with variation of electrolyte buffer solution NH4Cl, NH4OAc, NH4HSO4 dan (NH4)2SO4. The result of electrodeposition process showed that optimum condition electrodeposition process for 235U isotope was obtained currents 1.2 ampere with process time for 2 hours, and 300 µL volume feed with electrolyte buffer NH4HSO4 in pH 3,5. The results of the electrodeposition process was obtained 2.314 µg deposition of the isotope 235U with recovery of 99.91%. The condition optimum parameter above was used for electrodeposition process in determination of 235U isotope which contained in U3Si2/Al irradiated fuel element. The spectrometer alpha analysis was obtained weight of 235U isotope as 0.403 µg with recovery of 91.80%. The conclusion of this research, the electrodeposition methods is good enough to be used for determining 235U isotope in U3Si2/Al irradiated fuel plate.